2008
DOI: 10.2478/s11658-007-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemidesmus indicus Protects against ethanol-induced liver toxicity

Abstract: Alcoholic liver disease (ALD) is one of the most common diseases in modern society. A large number of studies are in progress aiming to identify natural substances that would be effective in reducing the severity of ALD. Although there are currently a number of drugs on the market, their long-term use can have numerous side effects. Hemidesmus indicus is an indigenous Ayurvedic medicinal plant used in soft drinks in India. In this study, we examined the effects of its ethanolic root extract on experimental liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
2
7
0
1
Order By: Relevance
“…In Indian ayurvedic medicine, the root extract has been used in beverages, as a blood purifier and to cure various liver disorders. Previous studies reported that alcoholic extract of its roots possess antiheptotoxicity, antithrombotic, antinociceptive, renoprotective, anti-inflammatory, antidiarrhoeal and antienterobacterial activities (Prabakan et al, 2000;Mary et al, 2003;Das et al, 2003;Kotnis et al, 2004;Verma et al, 2005;Das and Devaraj, 2006;Baheti et al, 2006;Saravanan and Nalini, 2008). This study, demonstrates a protective effect of aqueous extract of Hemidesmus indicus against the oxidative stress induced by bromobenzene in rat liver mitochondria.…”
Section: Introductionsupporting
confidence: 55%
“…In Indian ayurvedic medicine, the root extract has been used in beverages, as a blood purifier and to cure various liver disorders. Previous studies reported that alcoholic extract of its roots possess antiheptotoxicity, antithrombotic, antinociceptive, renoprotective, anti-inflammatory, antidiarrhoeal and antienterobacterial activities (Prabakan et al, 2000;Mary et al, 2003;Das et al, 2003;Kotnis et al, 2004;Verma et al, 2005;Das and Devaraj, 2006;Baheti et al, 2006;Saravanan and Nalini, 2008). This study, demonstrates a protective effect of aqueous extract of Hemidesmus indicus against the oxidative stress induced by bromobenzene in rat liver mitochondria.…”
Section: Introductionsupporting
confidence: 55%
“…Elevated bilirubin values are an indication of altered liver functions and a small elevation is an important indicator of liver damage in laboratory animals or could be a sign of biliary duct obstruction. Liver is the primary site for the synthesis of plasma proteins especially albumin and alterations in the total plasma proteins may indicate liver dysfunction [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that of A. calamus, the root extract of H. indicus also possesses strong antioxidant and radioprotective properties (Shetty et al, 2005). The root extract of this plant has been reported to be a potent chemopreventive agent in skin carcinogenesis (Sultana et al, 2003) and was also found to be effective against renal toxicity induced by ethanol and aminoglycoside antibiotics as well as ethanol-mediated hepatic toxicity in experimental animals (Kotnis et al, 2004, Saravanan & Nalini, 2007a, 2008. One of the major active principles in the root extract has been identified as 2-hydroxy 4-methoxy benzoic acid, which help to reduce the levels of liver collagen, hydroxyproline content, crosslinked fluorescence, shrinkage temperature and lipid peroxidation in ethanol-fed rats (Saravanan & Nalini, 2007b).…”
Section: Introductionmentioning
confidence: 99%